THE EFFECT OF BASEMENT FAULT REACTIVATION ON THE TRIASSIC – RECENT GEOLOGY OF KURDISTAN, NORTH IRAQ. (January 2015) - Burberry, C. M.
<x xml:space="preserve">Abstract</x> The Zagros orogenic belt is underlain by a complex faulted Precambrian basement. Major fault trends originating in this basement have been invoked to explain large‐scale structural changes along the strike of the orogen, e.g. the development of the Kirkuk Embayment (Kurdistan, Iraq) and the Lurestan Salient (Iran). However, within the Kirkuk Embayment, these structural trends have not previously been considered as an interacting group of faults which are periodically reactivated. This contribution first presents a revised basement fault map for the Kirkuk Embayment, created from interpreted gravity data, existing fault maps and remote sensing lineament analyses. This map is then compared to surface structure maps, published facies maps and source rock maturity data using GIS techniques. The object is to define the relationship between the basement faults and surface structures, fades and source‐rock maturity through time. Surface anticline orientation and location, as well as a number of major facies changes within the cover sequence, and the maturity of Triassic source rocks, are constrained by the interaction of the Najd and Transverse fault trends. A third basement trend, the Nabitah trend, has a more subtle effect on Phanerozoic geology. The Kirkuk Embayment can be divided into a series of semi‐independent basement blocks, defined by these basement fault trends. The interaction of these semi‐independent blocks has created local but predictable differences in surface structures, sediment thickness and facies, and variations in the maturity of Triassic source units across the Kirkuk Embayment. An understanding of the location and behaviour of basement faults within this hydrocarbon province is therefore a valuable predictive tool in exploration.